1993
DOI: 10.1113/jphysiol.1993.sp019581
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial control of the pulmonary circulation in normal and chronically hypoxic rats.

Abstract: 1. The effect of blockade of nitric oxide synthesis in pulmonary endothelium by two L-arginine analogues was tested in isolated blood-perfused lungs of normal rats and rats exposed chronically to 10% O2. 2. In both groups of rats the analogues (N-monomethyl-L-arginine (L-NMMA) and N-nitro-L-arginine methyl ester (L-NAME)) enhanced hypoxic vasoconstriction. In normal rats, with rare exceptions, these analogues had little or no effect on pulmonary artery pressure (Ppa) at constant blood flow during normoxia. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
70
4

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 11 publications
(16 reference statements)
9
70
4
Order By: Relevance
“…As described earlier, we and others found that NOS blockade did not raise Ppa in normoxic isolated perfused rat lungs (Mazmanian et al 1989;Archer et al 1990;Hasunuma et al 1991;Barer et al 1993). However, we found that it did raise Ppa during relatively mild hypoxia (7% Oµ ventilation; Barer et al 1993). Thus, in vivo, the mixed venous POµ may be sufficiently low to cause slight constriction and activation of NOS.…”
Section: Rat Lungsmentioning
confidence: 84%
See 1 more Smart Citation
“…As described earlier, we and others found that NOS blockade did not raise Ppa in normoxic isolated perfused rat lungs (Mazmanian et al 1989;Archer et al 1990;Hasunuma et al 1991;Barer et al 1993). However, we found that it did raise Ppa during relatively mild hypoxia (7% Oµ ventilation; Barer et al 1993). Thus, in vivo, the mixed venous POµ may be sufficiently low to cause slight constriction and activation of NOS.…”
Section: Rat Lungsmentioning
confidence: 84%
“…The circumstances which cause their release are not fully worked out and may differ with species. In isolated rat lungs perfused at constant flow, blockade of either NOS with the ¬_arginine analogues (Mazmanian et al 1989;Archer et al 1990;Hasunuma et al 1991;Barer et al 1993) or COX with sodium meclofenamate (Russell et al 1993) caused little or no rise in pulmonary artery pressure (Ppa); however, if the vasculature was in a state of vasoconstriction caused by vasoconstrictor agents or chronic exposure to hypoxia, ¬_NAME did cause a substantial rise in Ppa. These results suggest that, in these circumstances, there is no constant release of NO or dilator prostaglandins in the rat.…”
mentioning
confidence: 99%
“…As the half-life of NO is very short, we can suspect that the high rate of NO production is attained after diving. Hypoxic conditions are known to induce NO synthesis by endothelial cells (Barer et al, 1993;Swenson et al, 2005) in accordance with the increased plasma nitrite levels after diving apnea session. The lack of differences between placebo and supplemented groups could indicate that endothelial cells are saturated with ascorbate in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…NO is also continuously released in the systemic circulation and attenuates the arterial pressure [17]. Shear stress is a probable stimulus for NO release.…”
Section: Discussionmentioning
confidence: 99%
“…Shear stress is a probable stimulus for NO release. Hypoxic vasoconstriction may also provoke NO release in proportion to its severity [17]. The end metabolic product of NO is nitrite and nitrate.…”
Section: Discussionmentioning
confidence: 99%